(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
For a variety of applications it is desirable to produce textile materials with specially designed properties. Reinforcing 2D and 3D woven structures for fibers reinforced polymer composites were developed from renewable natural fibers and tested in this research work. Results and discussion are presented in the paper.